Gamifying Cybersecurity Knowledge to Promote Good Cybersecurity Behaviour - Faith B. Fatokun; Zalizah Awang Long; Suraya Hamid; Johnson O. Fatokun; Christopher Ifeanyi Eke; Azah Norman (Journal of Computing Technologies and Creative Content, 2022)
Cybersecurity is a major issue in contemporary times as security breaches are prevalent in organizations due to cyberattacks. The bulk of these attacks is caused by human errors as well as a lack of cybersecurity knowledge by online users. Though there is advancement in the provision of technological solutions to enhance online safety, humans are still very vulnerable to cybercrime. It is therefore important to consider novel and attractive ways to educate as well as spread awareness of cybersecurity knowledge that can help in enhancing good online behaviours and avoiding cyber threats. This paper via an exploratory approach proposes the gamifying of cybersecurity knowledge to promote good online behaviour. This is ongoing research that intends to develop a gamification model that will integrate cybersecurity knowledge and behaviour into one comprehensive immersion. Specifically, this paper discusses the components needed for the proposed model which will be presented in future works.